Pelatihan Pembelajaran Dan Penilaian Higher Order Thinking Skills (HOTS) dan Literasi Sains Bagi Guru IPA SMP - Sifak Indana; Wasis Wasis; Mukhayyarotin Niswati Rodliyatul Jauhari (Yayasan Keluarga Guru Mandiri, 2022)
The higher-order thinking skills of teachers and pre-service teachers can affect students' low scientific literacy. The purpose of this service is to strengthen insight and skills in designing learning and compiling questions on higher-order thinking skills and scientific literacy for science subjects in junior high schools. The specific objectives are to increase teachers' insight into HOTS and scientific literacy, to train teachers' skills in developing lesson plans that facilitate the growth of HOTS and scientific literacy, and to train teachers' skills in preparing assessment instruments. The activity was carried out face-to-face and was attended by 20 science teachers at state junior high schools in Nganjuk Regency. The training has produced products in the form of lesson plans, student activity sheets, and HOTS assessment instruments developed by the target teachers.